Preliminary Evaluation of Longitudinal Brain MRI Volumetric Quantification in Persons with Cognitive Decline and Confirmed Amyloid Burden Undergoing Multi‐Modal Interventions at an Outpatient Memory Clinic. (20th December 2022) - Meysami, Somayeh; Raji, Cyrus A.; Chwa, Won Jong; Popa, Emily S.; Ganapathi, Aarthi S.; Bookheimer, Tess; Slyapich, Colby B.; Pierce, Kyron P.; Richards, Casey J.; Gill, Jaya M.; Lampa, Melanie G.; Rapozo, Molly K.; et al.
Abstract: Background: Personalized multi‐modal interventions for Alzheimer dementia hold promise to slow progression of symptoms yet related quantitative neuroimaging biomarkers have not been investigated[1, 2]. Method: We selected 16 participants (mean age 68.6±5.9 [range 57‐77] years, 50% female) from the Pacific Brain Health Center at Providence St. John's Health Center, with biomarker evidence of Alzheimer dementia amyloidosis. All participants received data‐supported clinical recommendations (DSCR), [3–7] which included a modified SHIELD program[8] recommending a low carbohydrate diet. DSCRs were personalized based on clinical evaluations and laboratory values and closely overseen by a dementia specialist (DM, CW). T1‐weighted MR images were acquired at baseline and with a 1‐year average follow up. Total gray and white matter, hippocampal, lateral ventricle, temporal, parietal, occipital and frontal lobe volumes were quantified using Neuroreader[9]. Global cognition was tested using the Montreal Cognitive Assessment (MoCA). Paired t‐tests were done for these metrics. Result: Changes in hippocampal volumes (t=+1.6, p=0.11), temporal (t=+0.03, p=0.97) and frontal lobes (t=‐0.63, p=0.53) were not significant. There was a marginally significant decline in the parietal lobes (t=+2.1, p=.048) and statistically significant increased lateral ventricles (t=‐4.9, p<0.01). White matter volume declined significantly (t=‐2.8, p=0.01) while gray matter did not change significantly (t=+1.2, p=0.21). Table 1 shows annualized percent changes for these regions. These changes were attenuated compared to literature values for the following regions: gray matter at ‐2%/year [10], hippocampus at ‐3.5%/year [11], temporal lobes at ‐3.23%/year, parietal lobes at ‐3.62%/year and frontal lobes at ‐2.88%/year [12]. Total gray matter and frontal lobe volumes showed increased average annualized changes at +1.97%/year and +0.87%/year respectively. Over the same time period as the brain‐volume trajectory measurements, there was an average decline in MoCA (‐1.5 from 22.06±4.1 to 20.56±6.1, p=0.06) that trended towards but was not statistically significant. Conclusion: Regional volume loss, while present, was moderated compared to literature derived rates. Increased ventricular volumes appear driven by white matter volume loss. These preliminary data suggest that efforts to track and report on clinical outcomes in settings providing close medical management and multimodal lifestyle recommendations may be a worthwhile step towards validating research findings.